Informal digital learning of English (IDLE): a scoping review of what has been done and a look towards what is to come - Soyoof, Ali; Reynolds, Barry Lee; Vazquez-Calvo, Boris; McLay, Katherine (Computer assisted language learning, 2023)
As technology has advanced, so have opportunities for language socialization and practice. This reciprocal relationship has resulted in the emergence of a subfield of Computer Assisted Language Learning (CALL): Informal Digital Learning of English (IDLE). IDLE has manifested in various forms, including the more notable extramural and extracurricular varieties. Given the recent attention given to IDLE by Applied Linguists and language educators, this scoping review provides a roadmap for future research and explores the potential of IDLE to support English language teaching and learning in informal digital contexts. A Web of Science core eight database search for relevant research published between 1980 and 2019 using 35 IDLE-related key terms resulted in 38 studies of which 30 aligned with the inclusion criteria. Results showed the studies were conducted mostly under a mixed-method and qualitative paradigm and were published between 2017 and 2019. Only two studies used longitudinal data collection methods. Topics investigated included the linguistic dimension of CALL, the affective and cultural dimension of CALL, and the agency and digital literacies dimension of CALL. The small, yet salient, body of emergent IDLE literature points towards three trends: a growing relevance of langua-technocultural competence, the importance of digital literacies to communicative competence, and the importance of non-professional translation and interpreting to digital language learning.